Environmental Economics: The 50th Anniversary of the Birth of This Field around the First Earth Day - Don Fullerton (Center for Economic Studies and ifo Institute (CESifo), 2020)
How was the birth of "Environmental Economics" related to the first Earth Day fifty years ago (April 22, 1970)? This short note introduces some ideas about an amazing burst of intellectual activity from 1968 to 1974. Environmental economics was not a field of economics before this brief period, but the main field journal was up and running by the end of it. This note on "environmental economics" will be published in the forthcoming "Earth 2020: An Insider's Guide to a Rapidly Changing Planet" by Philippe D. Tortell (Cambridge: Open Book Publishers), along with a score of other notes about the fifty years of progress on air pollution, water, climate, oceans, fish, land, forest, biodiversity, plastics, contaminants, space junk, geo-engineering, media, law, and politics.
Keywords: Q20; Q30; Q40; Q50; 330; environment; policy; climate; Earth Day